PWE-002 Cell growth is impaired in a cellular model of non-alcoholic fatty liver disease, but is unaffected by simple steatosis. (23rd September 2015) - Gilchrist, E S; Lockman, K; Pryde, A; Cowan, P; Lee, P; Plevris, J N
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) is an important cause of cirrhosis. Cirrhosis can be considered as a state where disordered growth leads to inadequate repair and a risk of malignancy. We sought to study the growth characteristics of C3A cells in an in vitro model of NAFLD. Methods: C3A cells (well differentiated hepatoblastoma cells) were preconditioned for 72 h in control media, media containing oleate (which leads to steatosis, but not insulin resistance) or LPON media containing lactate (L), pyruvate (P), octanoate (O) and ammonia (N) (leading to steatosis, insulin resistance and increased reactive oxygen species). The cells were passaged and re-incubated in the appropriate media. Cells were harvested daily for cell counting and total protein estimation for 5 days. Cell cycle analysis and apoptosis estimation were performed on day 3. Results: Growth curves were established, showing by both cell counting and protein estimation that growth was significantly reduced in the NAFLD model (p< 0.0001) compared to control media and oleate (Abstract 002 Figure 1 ). Cell cycle analysis showed that cells grown in LPON did not accumulate in G0/G1, but appeared to accumulate in S phase (Abstract 002 Figure 2 ). Cells grown in oleate cycled normally. There was an increase in apoptosis in both oleate and LPON groups (26.1 and 27.7% cells undergoing apoptosis, compared to 13.5% of control cells, p<0.0001). Conclusion: NAFLD-induced cells showed significantly impaired growth compared with both control and simple steatotic cells in this model. This was not wholly attributable to an increase in apoptosis, as there was a similar increase in apoptosis with steatosis. While simple fat accumulation increased apoptosis, there was in addition, impairment of cell growth in our NAFLD model, which may be due to formation of reactive oxygen species, causing DNA damage and cell cycle arrest.